Multi-product, multi-level product control system analysis - Popplewell, Keith (1980)
Several techniques are applicable to the modelling of production and inventory control systems. In this thesis discrete linear control theory is examined as a method of modelling multi-product, multi-level systems. These systems are categorised and a general discrete linear control model is used to determine system stability and to predict system responses to specific patterns of input information. The response of the system to random variability in input or other system variable is also shown to be predictable. A library of sub-system models is provided and the method is illustrated by examples and a case study.